Pharmacokinetics of Once Versus Twice Daily Darunavir in Pregnant HIV-Infected Women. (1st September 2015) - Stek, Alice; Best, Brookie M.; Wang, Jiajia; Capparelli, Edmund V.; Burchett, Sandra K.; Kreitchmann, Regis; Rungruengthanakit, Kittipong; Cressey, Tim R.; Mofenson, Lynne M.; Smith, Elizabeth; Shapiro, David; Mirochnick, Mark
Abstract : Objective: To describe darunavir (DRV) pharmacokinetics with once-and twice-daily dosing during pregnancy and postpartum in HIV-infected women. Design: Women were enrolled in International Maternal Pediatric Adolescent AIDS Clinical Trials Network Protocol P1026s, a prospective nonblinded study of antiretroviral pharmacokinetics in HIV-infected pregnant women that included separate cohorts receiving DRV/ritonavir dosed at either 800 mg/100 mg once daily or 600 mg/100 mg twice daily. Methods: Intensive steady-state 12- or 24-hour pharmacokinetic profiles were performed during the second trimester, third trimester, and postpartum. DRV was measured using high-performance liquid chromatography (detection limit: 0.09 μg/mL). Results: Pharmacokinetic data were available for 64 women (30 once daily and 34 twice daily dosing). Median DRV area under the concentration–time curve (AUC) and maximum concentration were significantly reduced during pregnancy with both dosing regimens compared with postpartum, whereas the last measurable concentration (Clast) was also reduced during pregnancy with once daily DRV. DRV AUC with once daily dosing was reduced by 38% during the second trimester and by 39% during the third trimester. With twice daily dosing, DRV AUC was reduced by 26% in both trimesters. The median (range) ratio of cord blood/maternal delivery DRV concentration in 32 paired samples was 0.18 (range: 0–0.82). Conclusions: DRV exposure is reduced by pregnancy. To achieve DRV plasma concentrations during pregnancy equivalent to those seen in nonpregnant adults, an increased twice daily dose may be necessary. This may be especially important for treatment-experienced women who may have developed antiretroviral resistance mutations.